Impact of Earthquakes on the Transportation Infrastructure of Indonesia: A Preliminary Study - Anita Amirsardari; Massoud Sofi; Elisa Lumantarna; Iswandi Imran; Colin Duffield (Institute of Research and Community Outreach - Petra Christian University, 2019)
Indonesia is a high seismic region and one of the most vulnerable countries prone to experiencing damaging earthquakes. It is critical that lifeline infrastructure remain operational or is quickly remediated after an earthquake to minimise physical, social, and economical losses. Not much work has been carried out in understanding the effect of earthquakes on transportation infrastructure systems. This study aims to gain a better understanding of the impact of earthquakes on the transportation infrastructure in Indonesia. This is achieved by firstly reviewing the frameworks and tools for conducting seismic risk assessment of lifeline infrastructure. The critical components of the transportation system are then identified. Various forms of transportation infrastructure damage caused by earthquakes are discussed. An overview of the damaging earthquakes for the past 20 years is presented. Finally, conclusions and recommendations are provided about the future work required for conducting risk assessment of the transportation infrastructure in Indonesia